Transformasi Pendidikan di Amerika: Tantangan dan Inovasi di Era Digital - Silaban, Kiki Andiani; Situmorang, Grace Angelina; Batubara, Lois Zibya Priscilla; Sihombing, Masly; Situmorang, Maria Irma; Mutiara, Novia; Tungkup, Jopita Afnatasia Lumban (Polyscopia, 2024)
The digital era has significantly transformed various aspects of life, including education in the United States. This study examines the challenges and innovations arising from this digital transformation. Key challenges include the digital divide, the need for technology training for teachers, and adapting curricula to technological advancements. Conversely, innovations such as online learning, interactive learning tools, and the application of artificial intelligence in education hold great potential to enhance education quality. Utilizing case studies and recent data, this article provides a comprehensive overview of how America's education system navigates the digital age. The findings highlight the necessity for equitable access to technology, continuous professional development for educators, and curriculum reforms to integrate digital literacy. This study offers strategic recommendations for policymakers and educators to maximize the benefits of technology in education while addressing the ongoing challenges. By doing so, it aims to ensure that all students can benefit from the advancements in educational technology.